Procedure of creating activity-based costing system for higher education institutions in Oros Modeler environment - Januszewski, Arkadiusz (Procedura tworzenia systemu rachunku kosztów działań dla uczelni wyższej w środowisku Oros Modeler, 2011)
The article presents the procedure of building a computer-based costing systemde signed uniquely for university level education institutions. The concept of activity-based costing (ABC) has been adopted as the cost calculation method. The structure of the costing model for a hypothetic university has been elaborated and described in the paper. Significant attention has been paid to the implementation of the ABC model into the information technology environment. Thus, the most important steps of constructing the ABC system in the OROS Modeler environment have been described
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 156-167
Keywords: activity-based costing; ABC model; higher education; teaching costs